Factors affecting the implementation and sustainability of an Australian community-based doula service: A qualitative study - Sarah Min-Lee Khaw; Caroline S.E. Homer; Red Dearnley; Kerryn O'Rourke; Meghan A. Bohren (SSM: Qualitative Research in Health)
Background: Community-based doula support for women and gender-diverse birthing people has a range of benefits in improving maternal outcomes and experiences. However, there is limited research on how doula services operate in Australia. Birth for Humankind is an Australian community-based volunteer doula service, which provides free doula support for women and gender diverse birthing people experiencing social discrimination and financial disadvantage. The aim of this study was to understand facilitators and barriers to implementation and sustainability of a community-based doula service delivered to clients concurrently receiving care at a major maternity hospital in Melbourne, Australia. Methods: We conducted a qualitative study consisting of 30 in-depth interviews with doulas and managers of the community-based doula service Birth for Humankind, and midwives, doctors and social workers from a maternity hospital. Data were inductively thematically analysed, and themes were then deductively categorised using the Capability, Opportunity, and Motivation (COM-B) model and Theoretical Domains Framework (TDF) to understand behavioural influences and facilitators and barriers to implementing and sustaining the doula service within a hospital setting. Results: Facilitators to implementation of the doula service included: collaborative relationships; having sound knowledge of referral processes; and being a valued professional doula service with dedicated volunteers. Barriers to implementation included: limited knowledge of the doula service from hospital staff; difficulty in retaining volunteer doulas; being a small non-profit doula service; and limited capacity of hospitals to financially support the doula service. Advocacy for renumerating doulas may be one means to strengthen and sustain existing doula-provider service relationships. Conclusion: Consideration of establishing strategic partnerships between the doula service and hospitals may create financially-sustainable pathways to enable provision of high-quality, community-based doula support for women and gender diverse birthing people to continue.